Preventive Treatment with Methylprednisolone Paradoxically Exacerbates Experimental Autoimmune Encephalomyelitis - Simone Wüst; Jens van den Brandt; Holger M. Reichardt; Fred Lühder (International Journal of Endocrinology)
Glucocorticoids (GCs) represent the standard treatment for acute disease bouts in multiple sclerosis (MS) patients, for which methylprednisolone (MP) pulse therapy is the most frequently used protocol. Here, we compared the efficacy of therapeutic and preventive MP application in MOG35-55-induced experimental autoimmune encephalomyelitis (EAE) in C57Bl/6 mice. When administered briefly after the onset of the disease, MP efficiently ameliorated EAE in a dose-dependent manner. Surprisingly, MP administration around the time of immunization was contraindicated as it even increased leukocyte infiltration into the CNS and worsened the disease symptoms. Our analyses suggest that in the latter case an incomplete depletion of peripheral T cells by MP triggers homeostatic proliferation, which presumably results in an enhanced priming of autoreactive T cells and causes an aggravated disease course. Thus, the timing and selection of a particular GC derivative require careful consideration in MS therapy.